1985
DOI: 10.1159/000156226
|View full text |Cite
|
Sign up to set email alerts
|

Vocal Communication in Lion-Tailed Macaques (Macaca silenus)

Abstract: Investigations of vocal communication in captive groups of lion-tailed macaques (Macaca silenus) revealed a repertoire of 17 basic patterns. Sixteen of them were recorded and their physical parameters analysed by sonagrams. During a field study these results were verified and complemented, and additional data on the vocal behaviour of this species were gathered. The vocal repertoire of lion-tailed macaques is characterized by discretely structured, mostly interaction- and situation-specific sound patterns. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
24
0

Year Published

1990
1990
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 38 publications
4
24
0
Order By: Relevance
“…How well does the predicted and observed f 0 range overlap? The lowest f 0 of 80-100Hz corresponds to what has been reported in the literature (Green, 1975;Grimm, 1967;Lillehei and Snowdon, 1978;Hohmann and Herzog, 1985;Hauser, 1991;Hauser and Fowler, 1992;Owren et al, 1992;Owren and Rendall, 2003;Patel and Owren, 2007). The estimated maximum f 0 of ~2kHz fits many harmonic call types reported for rhesus monkeys, such as coo calls (Rowell and Hinde, 1962;Hauser, 1991;Owren and Rendall, 2003) or the girney call (Rowell and Hinde, 1962;Hauser and Fowler, 1992).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…How well does the predicted and observed f 0 range overlap? The lowest f 0 of 80-100Hz corresponds to what has been reported in the literature (Green, 1975;Grimm, 1967;Lillehei and Snowdon, 1978;Hohmann and Herzog, 1985;Hauser, 1991;Hauser and Fowler, 1992;Owren et al, 1992;Owren and Rendall, 2003;Patel and Owren, 2007). The estimated maximum f 0 of ~2kHz fits many harmonic call types reported for rhesus monkeys, such as coo calls (Rowell and Hinde, 1962;Hauser, 1991;Owren and Rendall, 2003) or the girney call (Rowell and Hinde, 1962;Hauser and Fowler, 1992).…”
Section: Discussionsupporting
confidence: 78%
“…The coo call is a typical vocalization of all species in the genus Macaca (Green, 1975;Grimm, 1967;Itani, 1963;Lillehei and Snowdon, 1978;Hohmann and Herzog, 1985;Hauser, 1991;Hauser and Fowler, 1992;Owren et al, 1992;Owren and Rendall, 2003;Rendall et al, 1996). Coo calls are approximately 500ms in duration.…”
Section: Introductionmentioning
confidence: 99%
“…This hypothesis is supported by a study of captive long-tailed macaques in which only one female came into estrus and copulated at any given time (Hohmann and Herzog 1985). Most other studies of macaques and baboons, however, have shown that multiple females can be receptive at the same time and emit copulation calls in conjunction with mating (e.g., O'Connell and Cowlishaw 1994; Nikitopoulos et al 2004).…”
Section: Hypothesis 7: Copulation Calls Advertise Mating To Other Femmentioning
confidence: 89%
“…breeding synchrony (Hohmann and Herzog 1985). This hypothesis is supported by a study of captive long-tailed macaques in which only one female came into estrus and copulated at any given time (Hohmann and Herzog 1985).…”
Section: Hypothesis 7: Copulation Calls Advertise Mating To Other Femmentioning
confidence: 90%
See 1 more Smart Citation